ANALISIS FAKTOR-FAKTOR KETERLAMBATAN PELAPORAN REALISASI ANGGARAN BLUD DI PUSKESMAS KABUPATEN BIMA - Mutmainnah, Nurul; Hidayatullah (LPPM AKADEMI MANAJEMEN ADMINISTRASI YOGYAKARTA, 2025)
This research analyzes the factors causing delays in the reporting of Budget Realization Reports (LRA) at BLUD Puskesmas in Bima Regency in 2023. Two main factors identified are the newly established BLUD status and the limited human resources (HR) in finance. Puskesmas, which was newly designated as BLUD in December 2021, faced difficulties in preparing financial reports according to procedures, with many staff members untrained in financial reporting. Additionally, the broad and diverse geographical location of Bima Regency, with some Puskesmas in remote areas with limited internet access, hindered the reporting process and caused delays. To address these challenges, the Bima Regency Health Office has taken steps such as providing guidance and assistance by BPKAD and Inspectorate teams, monthly reconciliation related to LRA, and the procurement of IT-based applications. This study uses a qualitative approach with a case study method, involving in-depth interviews, direct observation, and document analysis, which are analyzed using thematic analysis methods.